International Economic Concepts and Their Implementation in the Indonesian Context: Literature Study - M Leo Febriansyah; M Aidil Ramadhan; Fahmi Kurniawan; Dwi Agustin; Havis Aravik (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2025)
This research aims to understand and analyze the concept of international economics and how its implementation is related to the Indonesian economy. In facing global economic uncertainties such as trade wars, energy crises, and supply chain disruptions, Indonesia as a developing country needs to adopt appropriate strategies to maintain stability and enhance its economic competitiveness. By using a descriptive qualitative approach through literature study, this research examines various sources of literature such as books, academic journals, government reports, and reliable articles. The findings indicate that the implementation of international economics in Indonesia includes trade policies, foreign investment, export market diversification, as well as digital transformation and green industry. Indonesia also implements adaptive fiscal and monetary strategies, encourages industrial downstreaming, and strengthens regional and global economic cooperation. Through this approach, it is hoped that Indonesia can strengthen its position in the international market and achieve inclusive and sustainable economic growth.